A home from home: recursive nationhood, the 2015 STS television serial, Londongrad, and post-soviet stiob. Issue 2 (4th May 2017) - Hutchings, Stephen
ABSTRACT: Drawing on the mathematical concept of recursion as the repeated application of a single function to an initial element in a succession capable of indefinite extension, the article develops a recursive nationhood framework to capture the ongoing, mutual production of nationhood by the transnational, and nation by nation, in an extendable series of self-renewing repetitions which mirror and transform one another. Arguing that the framework has particular resonance for post-Soviet Russia, it explores one instance of recursive nationhood: the 2015 television serial, Londongrad, broadcast by Russia's STS channel. It analyses how, in the serial, transculturally generated images of Englishness, Russianness and Russian émigré-ness are recursively reprocessed and re-projected through one another in a self-conscious but circular hall-of-mirrors effect. The article concludes by linking recursive nationhood in Londongrad to a post-Soviet version of stiob, the peculiarly Russian form of self-parodic discourse which arose at the end of the Soviet period.